DIRECTIONS TO REDUCE ECONOMIC DISADVANTAGE AND ENSURE SUSTAINABLE ACTIVITIES OF ECONOMIC ENTITIES - Bo'riyeva Gulnoza Inat qizi (Ecominds Press, 2026)
This article analyzes in depth the factors leading to economic disadvantage of business entities, mechanisms for ensuring their financial stability and directions to reduce the risk of poverty. Aspects such as maintaining economic balance, risk management, rational use of internal and external resources of the enterprise, the effectiveness of state support mechanisms are highlighted. The article provides a justification for innovative management approaches for enterprises, factors to increase competitiveness, financial recovery strategies, and modern methods of crisis management. The article presents practical recommendations to strengthen economic stability of economic entities, effective organization of their activity and competitiveness in market conditions.
Keywords: Economic entities, economic disadvantage, financial stability, risk management, economic security, innovative management, wellness strategy, crisis management.